(untitled) (Journal of Forensic Medicine & Toxicology, 2021)
The COVID-19 pandemic caused by 2019-nCoV outbreaks in most of the countries has spread rapidly and became a major concern. Due to the strong infectivity nature of COVID-19 and lack of experience among forensic experts in performing autopsy during this period, it has been a challenge and a learning experience for the future. In this article, we summarize what are the issues faced and managed during and after medico-legal autopsy of confirmed or suspected cases.